Effects of genetic polymorphisms on the sulfation of doxorubicin by human SULT1C4 allozymes. (5th May 2021) - Gohal, Saud A; Rasool, Mohammed I; Bairam, Ahsan F; Alatwi, Eid S; Alherz, Fatemah A; Abunnaja, Maryam S; El Daibani, Amal A; Kurogi, Katsuhisa; Liu, Ming-Cheh
Abstract: Doxorubicin is a chemotherapeutic drug widely utilized in cancer treatment. An enzyme critical to doxorubicin metabolism is the cytosolic sulfotransferase (SULT) SULT1C4. This study investigated the functional impact of SULT1C4 single nucleotide polymorphisms (SNPs) on the sulfation of doxorubicin by SULT1C4 allozymes. A comprehensive database search was performed to identify various SULT1C4 SNPs. Ten nonsynonymous SULT1C4 SNPs were selected, and the corresponding cDNAs, packaged in pGEX-2TK expression vector, were generated via site-directed mutagenesis. Respective SULT1C4 allozymes were bacterially expressed and purified by affinity chromatography. Purified SULT1C4 allozymes, in comparison with the wild-type enzyme, were analysed for sulphating activities towards doxorubicin and 4-nitrophenol, a prototype substrate. Results obtained showed clearly differential doxorubicin-sulphating activity of SULT1C4 allozymes, implying differential metabolism of doxorubicin through sulfation in individuals with distinct SULT1C4 genotypes. Graphical Abstract: